2023
DOI: 10.3390/ejihpe13100152
|View full text |Cite
|
Sign up to set email alerts
|

Ramadan Fasting and Short-Term Maximal Physical Performance: Searching for Optimal Timing of the Last Meal “Suhoor” in Female Pre-University Handball Players

Houda Bougrine,
Atef Salem,
Nidhal Nasser
et al.

Abstract: Aiming to identify the ideal suhoor timing for maintaining optimal physical performance and health indicators during Ramadan intermittent fasting, the present study compares the effects of early vs. late Suhoor on short-term high-intensity physical exercise while controlling the body mass index (BMI) oral temperature (OT), dietary intake, and sleep patterns. In a randomized design, 19 female pre-university handball players (age: 16.8 ± 0.4 y; height: 1.70 ± 0.9 m; and body mass: 61.5 ± 6.9 kg) underwent two te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 82 publications
3
4
0
Order By: Relevance
“…Consistent with previous studies, our results did not reveal any evidence that alterations in body composition and nutrition during RIF could account for the adverse impact on cognitive performance ( 10 , 11 , 57 , 71 ). Contrary to a recent meta-analysis suggesting that maintaining training during RIF can lead to a reduction in body mass among adult athletes ( 72 ), our results are in agreement with the outcomes of another previous meta-analysis, which indicated that RIF does not have detrimental effects on body composition ( 73 ).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Consistent with previous studies, our results did not reveal any evidence that alterations in body composition and nutrition during RIF could account for the adverse impact on cognitive performance ( 10 , 11 , 57 , 71 ). Contrary to a recent meta-analysis suggesting that maintaining training during RIF can lead to a reduction in body mass among adult athletes ( 72 ), our results are in agreement with the outcomes of another previous meta-analysis, which indicated that RIF does not have detrimental effects on body composition ( 73 ).…”
Section: Discussionsupporting
confidence: 91%
“…RIF frequently causes sleep disturbances, which may contribute to a deterioration in cognitive function ( 59 ). Our results reveal a significant reduction in subjective sleep duration and quality during RIF, aligning with studies that associate cognitive decline with cumulative sleep deprivation and fragmentation throughout this month ( 10 , 11 ). Considering athletes may require more than the standard 7–9 h of sleep for optimal performance ( 60 ) and that partial sleep deprivation is known to compromise athletes' cognitive abilities, the decline in cognitive function observed in our study during the afternoon could partly be attributed to this phenomenon ( 61 , 62 ).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In line with prior studies on female athletes [ 58 , 59 , 60 ], the repeated sprint ability (RSA) test was conducted. The test involved six maximal 2 × 12.5 m shuttle sprints, each separated by 20 s of passive rest and 180° turns.…”
Section: Methodsmentioning
confidence: 99%